The drowning spool [large type] - Ferris, Monica (Ferris, Monica. Needlecraft mystery., 2014)
When the local senior complex, Watered Silk, asks Betsy to teach a class on the tricky punch needle technique, she jumps at the chance to win some new customers for Crewel World. It turns out the business opportunity that results isn't for the needlework shop. A young woman is found floating in the therapy pool, and Betsy's sleuthing skills are immediately called upon. But the list of suspects is more twisted than any Betsy has encountered before.